Combining Chitosan Nanoparticles and Garlic Essential Oil as Additive Fillers to Produce Pectin-Based Nanocomposite Edible Films - dos Santos, Vanessa Solfa [UNESP]; Lorevice, Marcos Vinicius; Baccarin, Graziela Solferini; da Costa, Fabíola Medeiros [UNESP]; da Silva Fernandes, Renan [UNESP]; Aouada, Fauze A. [UNESP]; de Moura, Márcia Regina [UNESP] (MDPI, 2023)
Edible films were produced by combining a pectin (PEC) matrix with chitosan nanopar-ticle (CSNP), polysorbate 80 (T80), and garlic essential oil (GEO) as an antimicrobial agent. CSNPs were analyzed for their size and stability, and the films, throughout their contact angle, scanning electron microscopy (SEM), mechanical and thermal properties, water vapor transmission rate, and antimicrobial activity. Four filming-forming suspensions were investigated: PGEO (control); PGEO@T80; PGEO@CSNP; PGEO@T80@CSNP. The compositions are included in the methodology. The average particle size was 317 nm, with the zeta potential reaching +21.4 mV, which indicated colloidal stability. The contact angle of the films exhibited values of 65°, 43°, 78°, and 64°, respec-tively. These values showed films with variations in hydrophilicity. In antimicrobial tests, the films containing GEO showed inhibition only by contact for S. aureus. For E. coli, the inhibition occurred in films containing CSNP and by direct contact in the culture. The results indicate a promising al-ternative for designing stable antimicrobial nanoparticles for application in novel food packaging. Although, it still shows some deficiencies in the mechanical properties, as demonstrated in the elongation data.
Keywords: biopolymers; garlic essential oil; nanoparticles; packaging